2019
DOI: 10.5937/turizam23-21325
|View full text |Cite
|
Sign up to set email alerts
|

Speleological approach for geotourism development in Zlatibor county (West Serbia)

Abstract: Western Serbia is a part of the Dinaric karst, which makes this area rich with caves, karst springs, karst waterfalls and other karst phenomena. Caves in the Zlatibor county, as representative speleological geosites, are one of the first established tourist caves in Serbia. They have great potential for speleotourism and geotourism development in the region and are considered important for tourism development of Zlatibor mountain. In this paper we analyze the speleological potential for geotourism development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Speleotourism flourished in the early 1980s, when it was reported that 26 million people visited caves around the world (Cigna 2016). By analyzing the available literature in the field of sustainable tourism and speleotourism (Tomić et al 2002;Antić 2018;Tičar et al 2018;Font et al 2019;Hall 2019;Nepal et al 2019;Tomić et al 2019;Vuković and Antić 2019), it can be concluded that the main objective of sustainable speleotourism would be to establish a healthy cave ecosystem, which fosters the co-presence of geomorphological, hydrological, biological, and anthropogenic factors and produces economic results for the local population.…”
Section: Sustainable Speleotourismmentioning
confidence: 99%
“…Speleotourism flourished in the early 1980s, when it was reported that 26 million people visited caves around the world (Cigna 2016). By analyzing the available literature in the field of sustainable tourism and speleotourism (Tomić et al 2002;Antić 2018;Tičar et al 2018;Font et al 2019;Hall 2019;Nepal et al 2019;Tomić et al 2019;Vuković and Antić 2019), it can be concluded that the main objective of sustainable speleotourism would be to establish a healthy cave ecosystem, which fosters the co-presence of geomorphological, hydrological, biological, and anthropogenic factors and produces economic results for the local population.…”
Section: Sustainable Speleotourismmentioning
confidence: 99%
“…This method has been efficiently applied numerous times for the assessment of various geosites in Serbia, Slovenia, USA, and Hungary. Antić et al [46] applied this model in assessing karst geoheritage in eastern Serbia, and other authors applied it for the evaluation of canyons and gorges [24,47], speleo-tourism potential [48][49][50][51], hydrological heritage [52], and other geological heritage [53][54][55][56][57][58].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A four-factor arrangement consisting of scientific research, art, technology and management is needed to prevent such negativities and to benefit from caves in a sustainable way (Cigna and Burri, 2000;Vuković and Antić, 2019). Some authors suggest that scientific research should be done first of these factors (Cigna, 2011;Cigna and Burri, 2000;Vuković and Antić, 2019). For this reason, the Karst system of Hayat Cave, which was not subject to a scientific research before, has been studied in a multifaceted way in this study.…”
Section: Introductionmentioning
confidence: 99%